Akhbārāt, 1181-1213 Hijrī, 1767-1799 ʻIsavī : ʻahd-i Navāb Mīr Niẓām ʻAlī Khān Bahādur - Khan, Yusuf Husain (Sainṭral Rikārds Āfis, 1955)
Chiefly on Indian political scene; during the reign of summaries of newsletters from different places of India, Mir Nizām ʻAlī Khān, Nizam of Hyderabad.